Characterization of the complete chloroplast genome of Thalictrum foliolosum DC. 1817, a folk medicine plant in China. Issue 4 (3rd April 2022) - Pu, Tingting; Zhou, Zhongyu; Zhang, Zhonglian; Zhang, Manchang
Abstract: Thalictrum foliolosum DC. 1817, a widely distributed species in the genus of Thalictrum, is used as a traditional herbal medicine in China. For the first time, the complete chloroplast (cp) genome of T. foliolosum was assembled and characterized for the first time in this study. The cp genome of T. foliolosum was 155, 764 bp in length, including a large-single copy region of 85, 086 bp, a small-single copy region of 17, 636 bp, and a pair of inverted repeats region of 53, 042 bp. The overall GC content was 38.50%. A total of 127 genes were predicted, including 82 protein-coding genes, 37 tRNA genes, and 8 ribosomal RNA genes. Phylogenetic analysis indicated that T. foliolosum is closely related to T. petaloideum .